Mark Twain's helpful hints for good living : a handbook for the damned human race - Twain, Mark, 1835-1910 (Twain, Mark, 1835-1910. Jumping frogs, 2004)
Irreverent, charming, eminently quotable, this handbook - an eccentric etiquette guide for the human race - contains sixtynine aphorisms, anecdotes, whimsical suggestions, maxims, and cautionary tales from Mark Twain's private and published writings. It dispenses advice and reflections on family life and public manners; opinions on topics such as dress, health, food, and childrearing and safety; and more specialized tips, such as those for dealing with annoying salesmen and burglars.